Global database of actual nitrogen loss rates in coastal and marine sediments - Y. Chang; E. Tan; D. Gao; C. Liu; Z. Zhang; Z. Huang; J. Liu; Y. Han; Z. Xu; B. Chen; S.-J. Kao (Earth System Science Data, 2025)
Denitrification and anaerobic ammonium oxidation (anammox) convert reactive nitrogen to inert N2 and play vital roles in nitrogen removal in coastal and marine ecosystems, weakening the adverse effects caused by terrestrial excessive nitrogen inputs. Given the importance of denitrification and anammox in the nitrogen cycle, several studies have measured denitrification and anammox through intact core incubations across different systems, and nitrogen loss processes are affected by a series of environmental factors such as organic carbon, nitrate, dissolved oxygen and temperature. However, a global synthesis of actual nitrogen loss rates is lacking, and how environmental factors regulate nitrogen loss remains unclear. Therefore, we have compiled a database of nitrogen loss rates, including denitrification and anammox in coastal and marine systems, from the published literature. This database includes 473, 466 and 255 measurements for total nitrogen loss, denitrification and anammox, respectively. This work deepens our understanding of the spatial and temporal distribution of denitrification, anammox and the relative contribution of anammox to total nitrogen loss, and their corresponding environmental controls. To our knowledge, the constructed database offers for the first time a comprehensive overview of actual nitrogen loss rates in coastal and marine ecosystems on a global scale. This database can be utilized to compare nitrogen loss rates of different regions, identify the key factors regulating these rates and parameterize biogeochemical models in the future. This database is available from the Figshare repository at https://doi.org/10.6084/m9.figshare.27745770.v3 (Chang et al., 2024).